Targeted long-read sequencing identified a causal structural variant in X-linked nephrogenic diabetes insipidus - Strych, Lukáš; Černá, Monika; Hejnalová, Markéta; Zavoral, Tomáš; Komrsková, Pavla; Tejcová, Jitka; Bitar, Ibrahim; Sládková, Eva; Sýkora, Josef; Šubrt, Ivan (BMC medical genomics, 2024)
Background X-linked nephrogenic diabetes insipidus (NDI) is a rare genetic renal disease caused by pathogenic variants in the AVPR2 gene. Single nucleotide variants and small insertions/deletions in AVPR2 are reliably detected by routine clinical sequencing. Nevertheless, structural variants involving AVPR2 are challenging to identify accurately by conventional genetic testing. Here, we report a novel deletion of AVPR2 in a Czech family identified for the first time by targeted long-read sequencing (T-LRS). Methods A male proband with X-linked NDI underwent clinical sequencing of the AVPR2 gene that failed and thus indicated possible whole-gene deletion. Therefore, PCR mapping and subsequent targeted long-read sequencing (T-LRS) using a Pacific Biosciences sequencer were applied to search for the suspected deletion. To validate the deletion breakpoints and prove variant segregation in the family with X-linked NDI, Sanger sequencing of the deletion junction was performed. Quantitative real-time PCR was further carried out to confirm the carrier status of heterozygous females. Results By T-LRS, a novel 7.5 kb deletion of AVPR2 causing X-linked NDI in the proband was precisely identified. Sanger sequencing of the deletion junction confirmed the variant breakpoints and detected the deletion in the probands´ mother, maternal aunt, and maternal cousin with X-linked NDI. The carrier status in heterozygous females was further validated by quantitative real-time PCR. Conclusions Identifying the 7.5 kb deletion gave a precise molecular diagnosis for the proband, enabled genetic counselling and genetic testing for the family, and further expanded the spectrum of structural variants causing X-linked NDI. Our results also show that T-LRS has significant potential for accurately identifying putative structural variants.